Water relations of Chusquea ramosissima and Merostachys claussenii in Iguazu National Park, Argentina - Saha, Sonali (2009)
Bamboos are prominent components of many tropical ecosystems, yet little is known about the physiological mechanisms utilized by these gigantic forest grasses. Here, we present data on the water transport properties of Chusquea ramosissima and Merostachys claussenii, monocarpic bamboo grasses native to the subtropical Atlantic forests of Argentina. C. ramosissima and M. claussenii differed in their growth form and exhibited contrasting strategies of water transport. Maximum xylem hydraulic conductivity of C. ramosissima culms was 2-fold higher than that of M. claussenii. C. ramosissima cavitated at relatively high water potentials (50% loss of conductivity at ≥1 MPa), whereas M. claussenii was more drought tolerant (50% loss at ≤3 MPa). Both species exhibited significant loss of hydraulic conductivity during the day, which was reversed overnight due to the generation of root pressure. The photosynthetic capacities of both bamboo species, estimated based on electron transport rates, were moderate, reflecting both the large amount of leaf area supported by culms and diurnal loss of hydraulic conductivity due to cavitation. Leaf hydraulic conductance was also relatively low for both species, congruent with their modest photosynthetic capacities. Within its native range, C. ramosissima is highly invasive due to its ability to colonize and persist in both forest gaps and land cleared for agriculture. We propose that a highly vulnerable vasculature, coupled with diurnal root pressure and an allometry that allows substantial leaf area to be supported on relatively slender culms, are key traits contributing to the ecological success of C. ramosissima.